Towards Sustainable Global Food Systems Conceptual and Policy Analysis of Agriculture, Food and Environment Linkages - Ruben, Ruerd; Verhagen, Jan (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
environment; food; agriculture; policy; global food systems